CoSense: Enhancing Sensemaking for Collaborative Web Search - Paul, Sharoda; Morris, Meredith Ringel (Proceedings of CHI 2009, 2009)
Making sense of the information found during an investigational Web search task can be daunting. With the recent emergence of tools to support collaborative Web search, the associated sensemaking task has become even more complex, requiring sense to be made not only of the products of a search (i.e., results found) but of the process, as well (i.e., group division of labor and decision-making). We present the findings of a formative study illustrating the sensemaking challenges posed by collaborative search tools. Based on these findings, we created CoSense, a system that supports sensemaking for collaborative Web search tasks by providing several rich, interactive views of a group’s search activities. We describe an evaluation of CoSense, reflecting on how its features supported different aspects of sensemaking, and how future collaborative search systems can benefit from these findings.
Best Paper Nominee